Sweat rate analysis of ivacaftor potentiation of CFTR in non-CF adults. Issue 1 (December 2018) - Kim, Jeeyeon; Farahmand, Miesha; Dunn, Colleen; Milla, Carlos; Horii, Rina; Thomas, Ewart; Moss, Richard; Wine, Jeffrey
Abstract To determine if ivacaftor (Kalydeco) influences non-CF human CFTR functionin vivo, we measured CFTR-dependent (C-sweat) and CFTR-independent (M-sweat) rates from multiple identified sweat glands in 8 non-CF adults. The two types of sweating were stimulated sequentially with intradermal injections of appropriate reagents; each gland served as its own control via alternating off-on drug tests on both arms, given at weekly intervals with 3 off and 3 on tests per subject. We compared drug effects on C-sweating stimulated by either high or low concentrations of β-adrenergic cocktail, and on methacholine-stimulated M-sweating. For each subject we measured 700 sweat volumes from 75 glands per arm (maximum 12 readings per gland), and sweat volumes were log-transformed for statistical analysis. T-tests derived from linear mixed models (LMMs) were more conservative than the familiar paired sample t-tests, and show that ivacaftor significantly increased C-sweating stimulated by both levels of agonist, with a larger effect in the low cocktail condition; ivacaftor did not increase M-sweat. Concurrent sweat chloride tests detected no effect of ivacaftor. We conclude that ivacaftorin vivo increases the open channel probability (PO ) of WT CFTR, provided it is not already maximally stimulated.